THE EFFECT OF CARBON TAXES, FOSSIL FUEL USE, AND GDP GROWTH ON CARBON EMISSIONS - Rahayu Kusumawati; Muhammad Heru Akhmadi (Program Sarjana Manajemen Universitas Internasional Batam, 2023)
This study examines the effect of carbon taxes, use of fossil fuels, and GDP growth on carbon emissions. The sample that we used is 12 European countries in the period 2016 – 2020. The analytical method used in this study is multiple linear regression analysis using panel data. The results of the study show that the use of natural gas and oil is a variable that influences carbon emissions which cause global warming. A 1% increase in the use of natural gas will increase carbon emissions by 0.24% and a 1% increase in the use of petroleum will also increase carbon emissions by 0.71%. This research also provides recommendations on fiscal policies that can be implemented in Indonesia related to the government's efforts to reduce carbon emissions.